Library management a practical guide for librarians - McCafferty, Bridgit, 1984- (Practical guides for librarians ;, 2021)
"This practical guide explores the different managerial roles at libraries, looking at the levels of managers, what they do, and how they do it. The book will help prepare early and mid-career librarians to step into new roles"--